2019
DOI: 10.15517/psm.v0i0.34404
|View full text |Cite
|
Sign up to set email alerts
|

Análisis retrospectivo de las lesiones de la mucosa oral entre 2008-2015 en el internado clínico de odontología de la Universidad de Costa Rica

Abstract: Objetivo: determinar la frecuencia de las diferentes lesiones de la mucosa oral en el internado clínico de la Facultad de Odontología de la Universidad de Costa Rica (UCR). Metodología: estudio retrospectivo de 263 informes de lesiones orales recuperados del archivo de biopsias de la Facultad de Odontología de la UCR del 2008 a 2015. Se evaluaron y analizaron de forma descriptiva y cualitativa información sobre el sexo, edad, localización de la lesión y diagnóstico histopatológico. Resultados: los casos de les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…We found 93 (62.0%) suffering from maxillary gingival swelling. Another study led by Carod-Artal et al also found maxillary gingival swelling among most epulis cases [19,20] . Chi-square test was applied for both fibrous epulis and pyogenic granuloma, and non-significant gender association was noted (p-value =0.160) as mentioned in Table-IV.…”
Section: Discussionmentioning
confidence: 86%
“…We found 93 (62.0%) suffering from maxillary gingival swelling. Another study led by Carod-Artal et al also found maxillary gingival swelling among most epulis cases [19,20] . Chi-square test was applied for both fibrous epulis and pyogenic granuloma, and non-significant gender association was noted (p-value =0.160) as mentioned in Table-IV.…”
Section: Discussionmentioning
confidence: 86%
“…These are considered responsible for about 50% of cases [6]. Data from a survey involving 90 patients, 21 smokers, and 27 alcoholics found precursor lesions of oral cancer such as actinic cheilitis and leukoplakia in ve and three patients, respectively [17]. They considered smoking and alcohol consumption to be the factors most associated with the appearance of cancer in the tongue and lip, both for active users and for those who stopped the habit [15].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research has been conducted worldwide on the epidemiological aspects of oral mucosal lesions (9,10); however, few studies have been carried out in Costa Rica (7,(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%